The identification, characterization, and management of Rotylenchulus reniformis on Cucumis melo in China - Qianqian Shi; Xinyue Cai; Ziqi Zhang; Wenwen Song; Chen Liang; Fangmeng Duan; Honghai Zhao (Phytopathology Research, 2023)
Abstract The reniform nematode, Rotylenchulus reniformis, is a sedentary root parasite that poses a significant threat to agricultural production in tropical and subtropical regions worldwide. In 2021–2022, a population of R. reniformis was identified in a melon greenhouse in Jimo District, Qingdao, China. To characterize this population, we employed morphological, morphometric, and molecular methods, which confirmed the identity of the nematodes as R. reniformis. Our investigation revealed that R. reniformis successfully infected the roots of melon plants and laid eggs, which could have led to significant crop damage. This report represents the first documented example of R. reniformis infecting melon plants in China. We evaluated several control strategies to combat this nematode, and our results indicated that soil solarization and the use of fosthiazate or chitooligosaccharide copper in combination with soil solarization were effective measures for managing R. reniformis in a greenhouse setting. In addition, combining soil solarization with chitooligosaccharide copper promoted melon plant growth and increased the relative abundance of microorganisms with biocontrol potential.